KEYNESIAN THEORY IN THE ”MACROECONOMICS“ COURSE FOR NON-CORE FACULTIES - T. I. Kurnosova; I. E. Rudakova (Vestnik MGIMO-Universiteta)
The article deals with the issues related to the teaching of Keynesian theory within the scope of macroeconomics course at the faculties of non-economic professions. It highlights the relevance of Keynes' ideas, the importance of the system approach typical for Keynesian theory that is in particular reflected in the understanding of the connection between economics large-scale processes on the whole and micro-level phenomena. The authors draw special attention to the importance of selecting the sections of Keynesian theory to be included in the economics short course in order to avoid overlooking the scientific significance of the material/data and to retain the essential achievements of the scientist. It refers to the balance of non-financial sector and labor market, to the idea of joint equilibrium in goods and money markets. Particular attention is dedicated to the recognition of the roles of both market and government stated by Keynes. This essential feature of the theory should be reflected in providing educational material. The authors underline that while studying the issues related to such terms as consumption, capital accumulation, investment and money demand, it is necessary to point out the role of psychological factors. These aspects of Keynesian analysis are of key importance for the economic processes' construction. Moreover, they have predetermined the direction of macroeconomics studies for the subsequent decades. Special attention in the article is also paid to the students’ motivation as one of the conditions for mastering the material taught.